Three Years Follow-Up of Single-Stage Correction with Modified Chula Technique for Frontoethmoidal Encephalomeningocele: The Advantage of The Teamwork Approach (A Case Report) - Lumintang, Loelita Marcelia; Niryana, I Wayan; Sanjaya, Hendra; Hamid, Agus Roy (Lingkar Studi Bedah Plastik Foundation, 2021)
Backgrounds: The main objective of Frontoethmoidal encephalomeningocele (FE) treatment are neural morbidities defect correction and aesthetically pleasing looks. Staged procedures are used to be performed in Indonesia. This article aimed to reveal the result of FE correction through the single-stage modified Chula technique (ST-MCT) procedure in collaboration with the neurosurgery team. Case Reports: A rare case of 5 years old girl diagnosed with FE was reported in this study. The FE was slowly increased in size, causing apparent facial deformity and the appearance of telecanthus. An ST-MCT procedure in collaboration with the neurosurgery team was conducted to correct the defects. The IOD values, IPD values, postoperative complications, and anesthetic improvements were evaluated in this study. Result: The patient was well after the surgery, with no complications and short length of stay. There were noted improvement of ICD, IOD and IPD postoperative follow up. At three years after the surgery ICD= 29mm; IOD= 26mm; IPD= 52 mm (normal range). Summary: ST-MCT procedure conducted in collaboration with neurosurgery team had shown excellent correction of ICD, IOD, and IPD values, no complication, shorter length of stay, and minimal scars. It considers as the most proper technique to reach a good result of correction and aesthetically pleasing looks in FE cases.